2010
DOI: 10.1371/journal.pone.0014240
|View full text |Cite
|
Sign up to set email alerts
|

O-Glycosylation Regulates Ubiquitination and Degradation of the Anti-Inflammatory Protein A20 to Accelerate Atherosclerosis in Diabetic ApoE-Null Mice

Abstract: BackgroundAccelerated atherosclerosis is the leading cause of morbidity and mortality in diabetic patients. Hyperglycemia is a recognized independent risk factor for heightened atherogenesis in diabetes mellitus (DM). However, our understanding of the mechanisms underlying glucose damage to the vasculature remains incomplete.Methodology/Principal FindingsHigh glucose and hyperglycemia reduced upregulation of the NF-κB inhibitory and atheroprotective protein A20 in human coronary endothelial (EC) and smooth mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 56 publications
0
50
0
Order By: Relevance
“…RIP1 is subject to proteasome degradation via K48-linked polyubiquitylation promoted by A20 (19). As hyperglycemia induces degradation of A20 (20) this may account for elevated RIP1 levels. The increased RIP1 may result in increased recruitment of RIP3 and MLKL (2).…”
Section: Discussionmentioning
confidence: 99%
“…RIP1 is subject to proteasome degradation via K48-linked polyubiquitylation promoted by A20 (19). As hyperglycemia induces degradation of A20 (20) this may account for elevated RIP1 levels. The increased RIP1 may result in increased recruitment of RIP3 and MLKL (2).…”
Section: Discussionmentioning
confidence: 99%
“…Shrikhande et al reported that hyperglycemia promotes the O-GlcNAcylation, ubiquitination, and degradation of A20, which accelerate atherosclerosis in diabetic mice (54). Interestingly, A20 has both ubiquitin ligase and deubiquitinase activities, suggesting that regulation of the A20 protein level by O-GlcNAcylation is a control point for the ubiquitination of A20 target proteins.…”
Section: O-glcnacylation Regulates Protein Ubiquitination Via Unknownmentioning
confidence: 99%
“…It was also speculated that an E1 ubiquitin-activating enzyme interacts with Hsp70 only in its O-GlcNAcylated form (Guinez et al 2008). An agonistic relationship between these two modifications is suggested such that O-GlcNAc may alter the activity of E1 enzymes to modulate stressinduced ubiquitination (Shrikhande et al 2010;Shimura et al 2001;Fujiki et al 2011). It has also been shown that OGlcNAcylation of a protein may facilitate its subsequent ubiquitination.…”
Section: Other Ptm Rolesmentioning
confidence: 99%